2021
DOI: 10.1155/2021/8897738
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of High-Sensitivity Troponin T for Subclinical Left Ventricular Systolic Dysfunction in Patients with Sepsis

Abstract: Background. Left ventricular systolic dysfunction (LVSD) is common in sepsis. Speckle-tracking echocardiography (STE) is a useful emerging tool for evaluating the intrinsic left ventricular systolic function. High-sensitivity cardiac troponin T (hs-cTnT) is the most sensitive biomarker of myocardial injury. However, there are limited data regarding the association between hs-cTnT level and left ventricular systolic dysfunction based on STE in septic patients. We performed this prospective study to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The fatality rate of children with tumor complicated with sepsis is even as high as 68%. In recent years, SOFA score has been widely adopted as the mean to identify patients with sepsis, and the relationship between SOFA and death risk has been fully verified Computational and Mathematical Methods in Medicine [27]. SOFA score indicators (such as creatinine or bilirubin levels) need to be tested in the laboratory; so, they cannot quickly capture the dysfunction of individual organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…The fatality rate of children with tumor complicated with sepsis is even as high as 68%. In recent years, SOFA score has been widely adopted as the mean to identify patients with sepsis, and the relationship between SOFA and death risk has been fully verified Computational and Mathematical Methods in Medicine [27]. SOFA score indicators (such as creatinine or bilirubin levels) need to be tested in the laboratory; so, they cannot quickly capture the dysfunction of individual organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Mehta et al found lower LVEF, higher incidence of regional wall motion abnormalities and higher mortality in patients with elevated cTNI levels in 37 patients presenting with septic shock [ 37 ]. Moreover, a study by Hai et al from 2021 found an association between high levels of hs-cTNT and left ventricular systolic dysfunction (LVSD), as measured by speckle-tracking echocardiography, in 116 patients with sepsis or septic shock [ 38 ]. Those results are also in line with a monocentric prospective study from 2022, finding high-sensitivity cTNI (hs-cTNI) and NT-pro BNP to be related to a risk for LVSD in 124 septic patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that plasma concentrations of hs-cTn, as a biomarker of myocardial injury, even correlate well with the functional abnormalities observed in echocardiography of patients with sepsis and septic shock in the first days of diagnosis, especially with diastolic dysfunction of the left ventricular and right ventricular dilation [11] and left ventricular systolic dysfunction [12]. In patients with septic shock, up to 65% of those with an elevated hs-cTnI level have various cardiac dysfunctions on transthoracic echocardiography and, more than the baseline level, a maximum change in hs-cTnI and ST waves-T on the electrocardiogram can be considered a risk factor for the development of SIMD [13].…”
Section: Introductionmentioning
confidence: 99%